Numeracy—an underestimated domain of adult basic education? - Anke Grotlüschen; Klaus Buddeberg; Gabriele Kaiser (Zeitschrift für Weiterbildungsforschung - Report, 2019)
Abstract In this article, terms and the state of research on adult numeracy are compiled in a systematic way. The findings and theories are selected according to their relation to the German-language discourse of adult education and at the same time embedded in a historical context as well as in international discourse. Many recent findings confirm Jean Lave’s approach in that numeracy differs from school mathematics in the high relevance of rules of thumb and estimates as well as in less formal procedures. Numeracy is therefore often not understood as mathematics and remains rather invisible. Numeracy practices are based on social power relations. The assertion of one’s own interests is also based on numeracy—for example in financial literacy, in the health system or in the use of statistical data. Last but not least, numeracy skills and practices go hand in hand with better living conditions.